Modelo dinâmico de um túnel de vento de sopro - Oliveira, Generoso Niederauer de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
Neste trabalho é desenvolvido e apresentado anteprojeto de Túnel de Vento de Sopro (TVS). Para esta finalidade foi desenvolvida ferramenta computacional para análise aerotermodinâmica para Túneis de Vento de Sopro. Neste âmbito é apresentado o estado da arte dos TVS, respectiva descrição sumária de TVS, principais problemas operacionais, pré-dimensionamento com base nos requisitos operacionais, formulação matemática do túnel e do respectivo sistema de controle. Também é feita a apresentação das ferramentas computacionais com base nos requisitos que possam validar a metodologia proposta e são apresentados resultados e respectivas análises destes resultados. Na parte final deste trabalho é apresentada a respectiva validação e os principais resultados obtidos com um anteprojeto de túnel acadêmico

In this work it is developed a basic design of a Supersonic Blowdown Wind Tunnel (SBDWT). For this purpose computer programs were developed for design and thermo-aerodynamics analysis for a SBDWT. In this framework it is presented the state of art of SBDWT, brief description of a SBDWT, its main operational problems, pre-design based on operational requirements, and tunnel’s mathematical formulation. Also it is described the computational programs based on tunnel’s requirements; results are presented, and the corresponding analysis is also discussed. At the last part of this work it is presented the assumptions made for the mathematical modeling, the main results obtained and the validation of the computer programs are emphasized, as well. A the last part of this work there is presented the respective validation and the main results got for an academic draft design of a wind tunnel
Keywords: Mecanica dos fluidos; Ar - Escoamento